Shipwreck ecology: understanding the function and processes from microbes to megafauna - Paxton, Avery; McGonigle, Christopher; Damour, Melanie; Holly, Georgia; Caporaso, Alicia; Campbell, Peter; Meyer-Kaiser, Kirstin; Hamden, Leila; Mires, Calvin; Taylor, J. Christopher (Oxford University Press (OUP), 2024)
An estimated three million shipwrecks exist worldwide and are recognized as cultural resources and foci of archaeological investigations. Shipwrecks also support ecological resources by providing underwater habitats that can be colonized by diverse organisms ranging from microbes to megafauna. Here, we review the emerging ecological subdiscipline of shipwreck ecology, which aims to understand ecological functions and processes that occur on shipwrecks. We synthesize how shipwrecks create habitat for biota across multiple trophic levels and then describe how fundamental ecological functions and processes, including succession, zonation, connectivity, energy flow, disturbance, and habitat degradation, manifest on shipwrecks. We highlight future directions in shipwreck ecology that are ripe for exploration, placing a particular emphasis on how shipwrecks may serve as experimental networks to address long-standing ecological questions.
Keywords: artificial habitat; archaeology; experimental network; maritime cultural heritage; underwater cultural heritage